2020
DOI: 10.1007/s00167-020-06307-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of rotator cuff repair in patients with mild to moderate glenohumeral osteoarthritis

Abstract: Purpose Osteoarthritis (OA) in the glenohumeral joint is a concomitant lesion with rotator cuff tear that commonly occurs in older patients. The authors aimed to evaluate the effect of associated OA on the treatment outcome of rotator cuff repair. Methods A total of three hundred and forty-eight patients who underwent full-thickness arthroscopic rotator cuff repair were retrospectively reviewed, and the data were prospectively collected. The severity of OA was evaluated using the Samilson and Prieto method pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…As such, most of the literature regarding RCR in patients with glenohumeral OA involves cases with mild OA. 17 , 18 However, a previous comparative study with this same patient cohort found that RCR may be a successful treatment with outcomes comparable with those without OA, and may still be a viable treatment option in patients with moderate-to-severe glenohumeral OA but with decreased strength and ROM outcomes compared with mild OA. 19 …”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…As such, most of the literature regarding RCR in patients with glenohumeral OA involves cases with mild OA. 17 , 18 However, a previous comparative study with this same patient cohort found that RCR may be a successful treatment with outcomes comparable with those without OA, and may still be a viable treatment option in patients with moderate-to-severe glenohumeral OA but with decreased strength and ROM outcomes compared with mild OA. 19 …”
Section: Discussionmentioning
confidence: 82%
“… 17 , 18 , 19 In addition, one study found no differences in range of motion (ROM), strength, or patient-reported outcomes between the 2 groups, 18 whereas others found slightly lower postoperative ROM among patients with glenohumeral OA. 17 , 19 …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two studies reported that patients with radiographically diagnosed GHOA preoperatively had worse postoperative PRO scores after RCR compared with those without preoperative GHOA. 15 , 17 In contrast, other studies found no difference in postoperative PROs between those with and without preoperative GHOA. 13 A recent study by Reddy et al 24 found no difference in revisions, retear rates, or PROs in patients with GHOA undergoing cuff repair compared with those without GHOA.…”
mentioning
confidence: 90%
“…A sizable subset of patients undergoing RCR may have preoperatively detectable GHOA, with reported rates ranging from 12.9% to 28% in the literature. 15 , 17 , 19 , 21 Most studies rely on radiographic scoring systems to diagnose GHOA, including the Samilson-Prieto, Kellgren-Lawrence, and Guyette systems. While these scoring systems have high inter- and intraobserver reliability, they classify GHOA based on joint space narrowing, osteophyte presence, and sclerosis, 26 which may be more difficult to detect in early disease.…”
mentioning
confidence: 99%